Dampak Debu Organik Serbuk Kayu Terhadap Penyakit Paru Obstruktif Akibat Kerja - Made Sherly Armiyanti (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: The impact of air pollution can occur in various aspects of life. Workers exposed to dust have a risk of experiencing health complaints and diseases, both infectious and non-infectious (cancer). Purpose: to find out more about the impact of organic wood dust which causes occupational obstructive pulmonary disease. Method: The method used by the author is a literature study from various national and international journals. This method is used with the aim of presenting, increasing knowledge and understanding of the topics discussed by summarizing material that has been published and providing factual information or new analysis from relevant literature reviews and then comparing the results in the article. Result: Wood dust organic dust can cause obstructive pulmonary disease in workers exposed to the dust. Conclusion: Wood dust organic dust can cause obstructive pulmonary disease in workers exposed to the dust. There are studies that say that one of the factors in the occurrence of occupational obstructive pulmonary disease is influenced by the amount of dust in the workplace and the length of exposure. For this reason, the use of PPE such as masks must be considered at work.